Potensi Spa dan Kuliner Lokal dalam Pengembangan Paket Ecowellness Tour Desa Wisata Nglanggeran - Ahmad, Halim; Wulandari, Lastiani Warih (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2026)
Nglanggeran Tourism Village offers a variety of tourist activity packages. Nglanggeran Tourism Village recently introduced a new package called a ecowellness tour, which includes a variety of activities like spa treatments, regional food choices, and meditation. In an attempt to gather feedback for enhancements so that a better ecowellness tour package is created, this study attempts to assess the new ecowellness tour package's implementation for the Nglanggeran Tourism Village. This study is a type of descriptive qualitative research in which descriptive data is extracted from expert respondents through the use of interviewing techniques. The Recreation Opportunity Spectrum (ROS) is the analytical instrument utilized in this study. The study's findings demonstrate that Nglanggeran Tourism Village has all the necessary attraction elements to be combined into ecowellness tour activity packages. This is made possible by human resources that are capable of adding value, have a drive to learn new things, and comprehend the fundamentals of customer service. According to the ROS analysis, the ecowellness tour package offered by the Nglanggeran Tourism Village falls under class II, or the accessible category. This indicates that the village has the experience, environment, and location advantage to offer ecowellness tour packages in the future.